2011
DOI: 10.1158/1055-9965.epi-10-1248
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Biomarker Profiles Differ Depending on Breast Cancer Subtype but RANTES Is Consistently Increased

Abstract: Background Current biomarkers for breast cancer have little potential for detection. We determined if breast cancer subtypes influence circulating protein biomarkers. Methods A sandwich-ELISA microarray platform was used to evaluate 23 candidate biomarkers in plasma samples that were obtained from subjects with either benign breast disease or invasive breast cancer. All plasma samples were collected at the time of biopsy, after a referral due to a suspicious screen (e.g., mammography). Cancer samples were ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…Many studies have measured the production of angiogenesis-related factors in serum from women with breast cancer via ELISA analysis; however, the majority of these have only examined one or two angiogenesisrelated factors, including VEGF (6,8,19,20), basic FGF (6), IL-6 (21), leptin and prolactin (8) and thrombospondin-1 (19). To date, there have only been three studies which have looked at the expression of multiple angiogenic factors in serum from women with breast cancer (10,12,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have measured the production of angiogenesis-related factors in serum from women with breast cancer via ELISA analysis; however, the majority of these have only examined one or two angiogenesisrelated factors, including VEGF (6,8,19,20), basic FGF (6), IL-6 (21), leptin and prolactin (8) and thrombospondin-1 (19). To date, there have only been three studies which have looked at the expression of multiple angiogenic factors in serum from women with breast cancer (10,12,22).…”
Section: Discussionmentioning
confidence: 99%
“…The process of angiogenesis is not the result of one single growth factor but rather is dependent on the interaction of multiple proteins with pro-or antiangiogenic properties. In breast cancer, like almost all other solid tumours, growth factors such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor (FGF), hepatocyte growth factor (HGF), platelet derived growth factor (PDGF), monocyte chemoattractant protein (MCP)-1, macrophage inflammatory protein (MIP)-1β, interleukin (IL)-8 and the regulated on activation, normal T cell expressed and secreted (RANTES), are expressed and, depending on Circulating levels of angiogenesis-related growth factors in breast cancer: A study to profile proteins responsible for tubule formation the subtype of breast cancer, have been identified as negative prognostic factors for patient survival (6)(7)(8)(9)(10). These growth factors may be responsible for inducing angiogenesis as they are pro-angiogenic, however, breast cancer cells and tissues can also produce inhibitors of angiogenesis, including thrombospondin, angiostatin and endostatin (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCL5 can be expressed and secreted either by cancer cells or by non-malignant stromal cells in the microenvironment. Investigations have indicated that CCL5 expression correlates with advanced BC, with greater plasma levels being found in patients with progressive and more advanced disease than those in remission [138]. Correspondingly, CCR5 expression is prerequisite for the induction of metalloproteinases by CCL5 in BC cells, thereby contributing to their invasive nature [139].…”
Section: The Role Of Chemokines In Tumor Metastasesmentioning
confidence: 99%
“…Our data suggest that the use of biomarker assays as an early-stage diagnostic test have been problematic due to the phenotypic diversity of breast cancer [12]. That is, five major subtypes of breast cancer have been identified based on both gene expression and protein profiles in tumor tissue [13–17], and these profiles are closely associated with traditional histological classifiers related to the overexpression of estrogen receptor (ER+) and/or the HER2 receptor (HER2+) [15, 18].…”
Section: Background and Motivationmentioning
confidence: 99%